Determinant of Sharia Stock price Evidence Sharia Stock Price in Indonesia and Malaysia - Syofi Aruni Mafaza; Atika Rukminastiti Masrifah; Eka Risana Putri; Anisa Rosdiana Zein (ISLAMICONOMIC: Jurnal Ekonomi Islam, 2022)
In attendance of sharia capital market shows that the improvement and development. It is can be considered from the majority moslems on investment. Then, the author attracted to compare the sharia stock price in both country. To determine the sharia stock price in Indonesia and Malaysia, it is caused by external factors and internal factors. The author attracted to analyze the determinant of stock price in both countries,the variables and systematic risk, that is EPS, BVPS, Dividend, and Beta. The researcher used panel regression in analyze nine companies in Indonesia and Malaysia. The result from this study shows that the fundamental factors which consist of EPS, BVPS, dividend, and beta have not significant impact on the sharia stock price in Indonesia although in Malaysia. They are many reason to explain the result of study. First reason, we used sharia stock in Indonesia which represented by JII and Malaysia which represented by FBHSM where both of capital market are sharia which the companies did not see on profit to determinant sharia stock price.  Second reason, it is totally different, when we do the research in sharia stock and if we considered from muslims insvestors perspective we conclude that the muslims investor more to prioritize the religious aspect than the other aspect. The different about sharia and conventional capital market are in screening method to determine the stock and sharia stock. Third reason, It is caused by the other factors from external